Environmentally sustainable management of water demands under changing climate conditions in the Upper Ganges Basin, India - Sapkota, P.; Bharati, L.; Gurung P; Kaushal N; Smakhtin, Vladimir U. (Wiley, 2013)
Allocation of water to cities, industries and agriculture has been a common practice in river basin planning and management. It is widely accepted that water also needs to be allocated for the aquatic environment, i.e. alongside the demands of other users. This paper describes the application of a basin planning model (Water Evaluation and Planning Model) to assess present and alternative water management options, which include incorporation of environmental flows (EFs) in the Upper Ganges River, India. Furthermore, the impacts of projected climate changes are also considered. The paper also briefly summarizes the EF assessment methodology, which was conducted through a multidisciplinary, multi-stakeholder approach (Building Blocks methodology). This is the first time that a comprehensive EF assessment has been done in India. Results from this study show that annual water demands for the domestic, industrial and irrigation water use are 1375, 1029 and 6680 MCM, respectively. Unmet demands, i.e. when there is not enough water to fulfil the required demands, were a problem during December and January for the past climate and during December, January and February under climate change-projected conditions. Adding EFs increased unmet demands in the same winter months. During March–November, unmet water demands were less than 5 MCM even with the addition of EFs. Reducing crop type to less water intense crops was more effective in reducing unmet demands than decreasing the cropped area. Improving irrigation systems through improved efficiency and water saving technologies as well as conjunctive use of surface and ground water is also viable options. However, the most effective water management solution is from managing upstream storage structures such as the Tehri dam for increased dry season flows. Dry season releases from Tehri dam can be used to reduce the downstream unmet demands, which include EFs to less than 5 MCM/month.